Discovery of 3, 6-disubstutited-imidazo[1, 2-a]pyridine derivatives as a new class of CLK1 inhibitors. (1st June 2021) - Zhang, Yun; Xia, Anjie; Zhang, Shiyu; Lin, Guifeng; Liu, Jingming; Chen, Pei; Mu, Bo; Jiao, Yan; Xu, Wenwen; Chen, Mingxin; Li, Linli
Graphical abstract: Abstract: Inhibition of cdc2-like kinase1 (CLK1) could efficiently induce autophagy and it has been thought as a potential target for treatment of autophagy-related diseases. Herein we report the discovery of a series of 3, 6-disubstutited-imidazo[1, 2- a ]pyridine derivatives as a new class of CLK1 inhibitors. Among them, compound 9e is the most potent one, which exhibits an IC50 value of 4 nM against CLK1 kinase. In vitro, this compound reduces the phosphorylation level of the typical downstream substrates of CLK1 and affects their subcellular redistribution. Further study indicates that 9e is efficient to induce autophagy. Overall, this study provides a promising lead compound for drug discovery targeting CLK1 kinase.